The partnership economy : how modern businesses find new customers, grow revenue, and deliver exceptional experiences - Yovanno, David A. (John Wiley & Sons, Inc., 2022)
"Traditionally marketing/business partnerships were limited to affiliates' revenue and transaction-based relationships designed to drive customer acquisition though loyalty programs, couponing or sampling. Today's partnership ecosystem has expanded to include creative collaborations across the entire customer journey. For example, a Spotify and Ticketmaster partnership enables Spotify customers to purchase Ticketmaster-distributed tickets for their favorite artists' events directly in the Spotify app. Similarly, influencers like Fashionista introduce vetted products such as Harry's razors to their followers' blogs. Partnerships like these enhance your customer experience, grow revenue, and help you connect with potential and existing customers you can't reach through traditional channels. This book explains how to grow revenue by expanding your business partnerships. It will be a quick and easy read, filled with key frameworks, stories, examples, and 'how to' suggestions"--